Availability and use of fodder shrubs and trees in tropical Africa - Atta-Krah, A.N. (1990)
Generally, trees occupy a significant niche in the farming systems and overall way of life in tropical Africa. Fodder shrubs and trees (browse) in this region play a significant role both in farming systems, where they are protected as fallow species, and in livestock production. Livestock in this zone depend largely on browse for their dietary protein. Compared with tropical grass, browse is generally richer in protein and minerals. The importance of browse increases with increasing aridity and is generally most essential in the dry seasons, when most other feed resources depreciate in quality and quantity. Browse intake increases total dry matter intake, increases crude protein intake, and improves the digestibility of low-quality forages. The effect of browse feeding on livestock is shown in increased survivability (i.e., lower mortalities, especially over the dry season) and increased productivity. Traditionally, throughout tropical Africa, processing and conservation of tree fodder is uncommon, and cultivation is minimal and insignificant. This paper advocates the need for increased cultivation and integration of fodder trees (especially leguminous ones) into local farming systems through agroforestry. It also stresses the need for increased research support for the efficient cultivation, management, and use of fodder shrubs and trees for improved livestock production.